2004
DOI: 10.1073/pnas.0401342101
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of folates in plants through metabolic engineering

Abstract: Humans depend on plants as a major source of dietary folates. Inadequate dietary levels of the vitamin folate can lead to megaloblastic anemia, birth defects, impaired cognitive development, and increased risk of cardiovascular disease and cancer. The biofortification of folate levels in food crops is a target for metabolic engineering. Folates are synthesized de novo from pterins and para-amino benzoic acid, which are subsequently combined to form dihydropteroate, the direct precursor to dihydrofolate. We pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 49 publications
(30 reference statements)
3
92
0
Order By: Relevance
“…The mammalian-type GCHI that we introduced was predicted to be free of feedback control in planta (13,22) and was highly effective in increasing flux to pteridines, which reached levels 140 times the average value in control fruit. The same basic strategy, but using bacterial GCHI, was similarly successful in enhancing pteridine production in Arabidopsis leaves (16). The folate synthesis intermediates dihydroneopterin, dihydromonapterin, and hydroxymethyldihydropterin were among the pteridines that accumulated in GCHI ϩ tomatoes, showing that the three enzymes directly downstream of GCHI all remain active in ripening fruit and can accommodate increased flux (these enzymes are the two that dephosphorylate dihydroneopterin triphosphate and dihydroneopterin aldolase; see Fig.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The mammalian-type GCHI that we introduced was predicted to be free of feedback control in planta (13,22) and was highly effective in increasing flux to pteridines, which reached levels 140 times the average value in control fruit. The same basic strategy, but using bacterial GCHI, was similarly successful in enhancing pteridine production in Arabidopsis leaves (16). The folate synthesis intermediates dihydroneopterin, dihydromonapterin, and hydroxymethyldihydropterin were among the pteridines that accumulated in GCHI ϩ tomatoes, showing that the three enzymes directly downstream of GCHI all remain active in ripening fruit and can accommodate increased flux (these enzymes are the two that dephosphorylate dihydroneopterin triphosphate and dihydroneopterin aldolase; see Fig.…”
Section: Discussionmentioning
confidence: 91%
“…The validity of this approach has been demonstrated in food-grade lactic acid bacteria, in which engineering tripled folate production (10). Because the plant folate synthesis pathway is now known (2,(11)(12)(13)(14)(15), folate engineering can be attempted with plants, and several groups have begun doing this (16)(17)(18)(19). We have chosen to engineer the folate pathway in tomatoes, in view of their worldwide importance as a food crop, their well developed molecular genetics, and their relatively low folate content (3,13).…”
mentioning
confidence: 99%
“…H 4 BPt does not occur in plants (Kohashi et al, 1980;Díaz de la Garza et al, 2004;Hossain et al, 2004), but it is widely used to assay the activity of AAHs for which it is not the in vivo cofactor (Leiros et al, 2007;Siltberg-Liberles et al, 2008;Pey and Martinez, 2009). Tests with the natural (R) and unnatural (S) forms of H 4 BPt showed that only the R form was active and that the S form had no inhibitory activity (see Supplemental Figure 4 online).…”
Section: Biochemical Characterization Of Pine and Moss Aahsmentioning
confidence: 99%
“…The main plant pterins are the folate synthesis intermediates dihydroneopterin, dihydromonapterin, and hydroxymethyldihydropterin (Kohashi et al, 1980;Díaz de la Garza et al, 2004; Hossain et al, 2004;Orsomando et al, 2006). These might be reduced to the tetrahydro level by a dihydropterin reductase like those in bacteria or protists (Gourley et al, 2001;Pribat et al, 2010).…”
Section: Identity Of the Physiological Cofactormentioning
confidence: 99%
“…3C), and increased GCH1 activity only affects the cytosolic (pterin) branch. In previous studies, the overexpression of GCH1 has resulted in massive increases in pterin levels but only a doubling of folate levels, presumably because the plastidial p-aminobenzoate (PABA) branch was depleted (20,21). Similar limitations affected plants with the PABA branch enhanced by overexpression of aminodeoxychorismate (ADC) synthase (ADCS), reflecting depletion of the pterin branch (22).…”
Section: Analysis Of Folate Levels In Transgenic Plants the Expressimentioning
confidence: 94%